Automotive emissions regulations and exhaust aftertreatment systems - Kasab, John; Strzelec, Andrea (SAE International, 2020)
The objective of this book is to present a fundamental development of the science and engineering underlying the design of exhaust aftertreatment systems for automotive internal combustion engines. No pre-requisite knowledge of the field is required: our objective is to acquaint the reader, whom we expect to be new to the field of emissions control, with the underlying principles, control methods, common problems, and fuel effects on catalytic exhaust aftertreatment devices. We do this in hope that they can better understand the previous and current generations of emissions control, and improve upon them. This book is designed for the engineer, researcher, designer, student, or any combination of those, who is concerned with the control of automotive exhaust emissions. It includes discussion of theory and fundamentals applicable to hardware development.
Includes index.
Keywords: Automobiles -- Motors -- Exhaust gas.; Automobiles -- Pollution control devices.; Environmental engineering.; elektronické knihy; electronic books